ESTIMATING SPATIAL DENSITY OF CLOSE BINARY SYSTEMS WITH SUB GIANT SECONDARIES IN SOLAR NEIGHBORHOOD - Eretnova, O. V. (Одеські астрономічні публікації, 2017)
The spatial density of close binary systems with subgiant secondaries in solar neighborhood are evaluated taking into account the effects of observational selection. It was found to be about 0.00018 pc- 3 or about 0.00035 M☉ pc-3.